1982
DOI: 10.1111/j.1471-4159.1982.tb10853.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Inhibitors of GABA‐Transaminase for the Determination of GABA Turnover in Mouse Brain Regions: An Evaluation of Aminooxyacetic Acid and Gabaculine

Abstract: The accumulation of γ‐aminobutyric acid (GABA) after inhibition of GABA‐T (4‐aminobutyrate: 2‐oxoglutamate aminotransferase, EC 2.6.1.19) by various doses of aminooxyacetic acid (AOAA) and gabaculine was studied in four different regions of the mouse brain. The dose‐response curve for GABA accumulation after treatment with AOAA was linear up to 10 mg/kg i.p., and then leveled off. The increase in GABA accumulation after gabaculine treatment was linear up to 100 mg/kg i.p. No further increase was observed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(39 citation statements)
references
References 38 publications
4
35
0
Order By: Relevance
“…This approach has been used by several other groups (e.g. Bernasconi et al, 1982) and in the current studies has been found to produce comparable data to that obtained using the technique of gas chromatography -mass spectrometry (mass fragmentography) coupled with infusion of ["Cl-glucose (Bertilsson & Costa, 1976). Some of the findings have been reported in preliminary form to the British Pharmacological Society (Green et al, 1985).…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…This approach has been used by several other groups (e.g. Bernasconi et al, 1982) and in the current studies has been found to produce comparable data to that obtained using the technique of gas chromatography -mass spectrometry (mass fragmentography) coupled with infusion of ["Cl-glucose (Bertilsson & Costa, 1976). Some of the findings have been reported in preliminary form to the British Pharmacological Society (Green et al, 1985).…”
Section: Introductionsupporting
confidence: 68%
“…Nevertheless the technique of GABA transaminase inhibition does give a good indication of changes in GABA synthesis rate following drug administration since GABA transaminase is the major degradation pathway for the transmitter (Loscher, 1980). Bernasconi et al (1982) demonstrated that amino-oxyacetic acid (AOAA) was arguably the best drug to use, being a more rapid inhibitor than gabuculline and further suggested, in contrast to the data of Walters et al (1978) Bernasconi et al, 1982) Roberts & Simonsen (1963). Brain regions were rapidly removed from rats killed by thoracic stun and decapitation and homogenised at a concentration of 10mg ml-' in the following mixture (hippocampi were pooled from two animals): potassium phosphate buffer (50mM), pH 6.4 containing 0.025% w/v EDTA; 0.…”
Section: C) the Macmillan Press Ltd 1987mentioning
confidence: 99%
“…At the end of HX-III, animals were injected with 3-MPA (IP-3-mercaptopropionic acid, an inhibitor of glutamic acid decarboxylase, a GABA-synthesizing enzyme; 100 mg/kg i.p.) to prevent postmortem formation of GABA [17,19]. Two minutes later they were sacrificed by decapitation.…”
Section: Methodsmentioning
confidence: 99%
“…Since AOAA inhibits GABA-T, the amount of GABA accumulated after AOAA is assumed to represent the amount of GABA synthesized [17]. Accumulation of GABA after AOAA is linear for 2 h after the injection [19].…”
Section: Concentrations Of Gabamentioning
confidence: 99%
See 1 more Smart Citation